Characterizing Landscape Fragmentation of Koitobos River Sub-Basin-Trans-Nzoia, Kenya - Murunga, Kennedy Wekesa; Nyadawa, Maurice; Sang, Joseph; Cheruiyot, Charles (Heliyon, 2023)
The changes of landscape structure and functioning due to unprecedented human interference is hastening across the globe and it is thus a compelling necessity to preserve and restore our ecosystems. This study aimed to characterize levels of landscape fragmentation, habitat structure, driving forces and perceptions of the residents on most preferred reconfiguration approaches. The land use/ land cover (LULC) change was first determined by interpreting the 1973, 1986, 1995, 2002, 2014 and 2022 Landsat images using the QGIS 3.26 while the selected landscape fragmentation metrics were analyzed using FRAGSTATS 4.2. Forests, shrubs, grasslands showed a declining trend, except agriculture, water and built-up areas, which depicted high increases for the study periods (1973 to 2022). The landscape of the study area is characterized as progressively fragmenting as signified by high escalated values of patch number (374 %), edge density (7828 %) between 1986 and 2002, contagion (10.3%), and a declined value of Shannon Diversity Index (SHDI) (-17.42%), Shannon evenness index (SHEI) (-25.8 %) and connectiveness (-43.3%). Considering these results, high losses of forests and grasslands coupled with expansive farmlands and built-up areas have led to unprecedented landscape fragmentation From field surveys and oral interviews, this has not only left streams vulnerable to massive sediment loads but has also triggered annual floods which occur during wet months even though change in onset of rainfall seasons was also reported. The findings call for restoration an integrated and sustainable restoration efforts especially for the forests, grasslands, riparian corridors. Along sustainable urban planning and community-based sensitization on watershed management
Keywords: Landscape Fragmentation; Fragmentation Indices; Watershed Heterogeneity; Land-Use Policy